(untitled) (Journal of Global Arts Studies, 2023)
Background: The purpose of rural revitalization is to promote the prosperity of rural industries and the prosperity of villagers. Building a digital supply chain in rural areas is one of the important paths to achieve the grand goal. Objective: To propose suggestions for the digital supply chain of rural agricultural and forestry products, build a stable and sustainable digital supply chain, cultivate rural industries and optimize industrial structure, enrich rural areas, and achieve rural revitalization. Methods: Through on-site interviews with village and town officials, farmers, and rural enterprises, had grasped the current situation and problems of the development and construction of rural industrial chains, the demand of agricultural and forestry products, with the demand sort out the digital supply chain of rural agricultural and forestry and element, calculate the weights by Analytic Hierarchy Process model, form a digital supply chain network structure with clear primary and secondary analysis and hierarchy. Results: We have built a digital supply chain network system with leading enterprises as the core, multi subject collaborative education, and suitable for the actual development of rural economy. We have elaborated on the key points of rural digital supply chain construction, from construction planning and digital supply chain design, to demand visualization, digitalization of planting and processing, modernization of cooperative operation, digitalization of logistics, and digitalization of risk management. Conclusion: Practice has proven that digital technology has significant application value in promoting rural revitalization, improving the living standards of villagers, and building beautiful rural areas, achieving overall rural prosperity and achieving comprehensive revitalization of industries, organizations, talents, culture, and ecology.